100 Jahre akademische Psychologie in Hamburg. Eine Festschrift - Spieß, Martin (Hamburg University Press, 2014)
period of time that encompasses the two World Wars, a Cold War and the transformation from the Empire through the "Third Reich" to democracy, the department has not only remained in Hamburg, but has also differentiated and developed considerably. On the occasion of this jubilee, the Department of Psychology documents in this volume some of the developmental stages of academic psychology in Hamburg. The contributions by Kurt Pawlik, Bernhard Dahme, Manfred Amelang, Frank Rösler, Martin Spieß and Tania Lincoln tell the story of academic psychology in Hamburg from very different, subjective perspectives.Paul Probst's contributions to the beginnings of academic psychology in Hamburg with Ernst Meumann and William Stern are an exception.The volume has been published by Kurt Pawlik and Bernhard Dahme as editors of a documentary on institutional and personnel development in academic psychology at the University of Hamburg since 1950.